If all is cozy, what isn’t? Some conceptual problems regarding cozy games - de Pan, Gideon; Bosman, Frank (Into the Magic Circle: Rethinking Homo Ludens, 2024)
The emergence of ‘cozy games’ as a distinct game category gives rise to some fundamental questions about this category’s formal qualifications regarding ludic and narrative elements (including ludonarrative dissonance), players’ experiences, developers’ intentions, and definitions of other constituent characteristics. Interpreting video games as digitally mediated ludo-narrative texts and employing a communication-oriented methodology, the two authors analyze, as case studies for their reflections on the problematic nature of the category, two well-known (if not unproblematic in their identification) ‘cozy games’ – Gris (Nomada Studio 2018) and Spiritfarer (Thunder Lotus Games 2021): both games are identified as ‘cozy’ by critics and players, but – quite paradoxically – deal with not-so-cozy subject matters like death, dying, and grief.